Ooencyrtus (Hymenoptera: Encyrtidae), egg parasitoids of the pistachio green stink bugs (Hemiptera: Pentatomidae) in Iran - Hayat, Mohammad; Mehrnejad, M. Reza (Zootaxa, 2016)
This paper deals with three species of Ooencyrtus Ashmead (Hymenoptera: Encyrtidae) obtained from eggs of the green stink bug, Brachynema germarii (Kolenati) (Hemiptera: Pentatomidae) infesting pistachio plants in Iran. Two new species, Ooencyrtus iranicus Hayat & Mehrnejad, sp. nov. and O. pistaciae Hayat & Mehrnejad, sp. nov., are described, and O. telenomicida (Vassiliev) is newly recorded from Iran, redescribed and illustrated. A key to some species considered similar to the species treated here is also given.